Prognostic biomarker CCR6 and its correlation with immune infiltration in cutaneous melanoma - Nurzat, Yeltai; Dai, Damao; Hu, Julong; Zhang, Feiyu; Lin, Zaihuan; Huang, Yang; Gang, Liang; Ji, Hang; Zhang, Xiaowen (Frontiers in Oncology, 2023)
Background: Cutaneous melanoma (CM) is an aggressive type of skin cancer. Even after standard treatment, the recurrence and malignant progression of CM were almost inevitable. The overall survival (OS) of patients with CM varied widely, making it critical for prognostic prediction. Based on the correlation between CCR6 and melanoma incidence, we aimed to investigate the prognostic role of CCR6 and its relationship with immune infiltration in CM. Methods: We obtained RNA sequencing data from “The Cancer Genome Atlas” (TCGA) to analyze the CM expression. Functional enrichment analyses, immune infiltration analyses, immune checkpoint analyses, and clinicopathology analyses were performed. Univariate and multivariate Cox regression analyses were used to identify independent prognostic factors. And nomogram model had been developed. Kaplan–Meier survival analysis and log-rank test were used to estimate the relationship between OS and CCR6 expression. Results: CCR6 was significantly up-regulated in CM. Functional enrichment analyses revealed CCR6 was correlated with immune response. Most immune cells and immune checkpoints were positively correlated with CCR6 expression. The Kaplan–Meier analyses showed that high CCR6 expression was associated with a good outcome in CM and its subtypes. The Cox regression showed CCR6 was an independent prognostic factor in patients with CM (HR = 0.550, 95%CI=0.332-0.912, P＜0.05). Conclusions: CCR6 is considered to be a new prognostic biomarker for patients with CM. And our study provide a potential therapeutic target for CM treatment.